Shifting landscapes the making and remaking of village commons in India - Brara, Rita. (New Delhi ; Oxford : Oxford University Press, 2006)
This is a high quality ethnographic study in the classical sense. The fundamental question that Brara asks is whether there are other ways of thinking about the village than in terms of its distinctions of caste, vertical ties created by patron-client relations of congregation of private propertied peasantry. She offers the idea that villagers can and do represent and act on matters of common concern but that this does not commit us to thinking of village communities as harmonious wholes.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Commons -- India -- Rajasthan -- Management; Natural resources, Communal -- India -- Rajasthan -- Management; Right of property -- India -- Rajasthan; Pasture, Right of -- India -- Rajasthan